Impact of Different Extension Teaching Methods for Adoption of Scientific Package of Practices of Chickpea - Patel, Diksha; Singh, Shyam; Verma, Arjun Prasad; Gupta, B.K.; Singh, Manvendra (Indian Journal of Extension Education, 2019)
Chickpea is the main rabi pulse crop under rainfed condition in Bundelkhand region of Uttar Pradesh. There is wide variation in the yield of chickpea across the 7 districts of Bundelkhand region of U.P. because of the low adoption of recommended package of practices of chickpea among the farming community. To accelerate adoption among farming community extension teaching methods plays a crucial role. Krishi Vigyan Kendra, Banda has initiated the on farm trial on impact assessment of different extension teaching methods for adoption of scientific package of practices of chickpea. The experimental research design pre and post with control group was used to conduct this study. In this study one control group (check) of 10 farmers was kept and one training on scientific package of practices of chickpea and demonstration (Cluster Frontline Demonstration) on chickpea was given to 10-10 farmers and their level of adoption of scientific package of practices of chickpea crop was assessed and it was found that the level of adoption has increased by 15.65 and 24.82 per cent after exposure to training and demonstration respectively to the farmers and both the methods were found to be significant at 0.01 level of significance for enhancing level of adoption among farmers. Therefore, potentialities of these methods could be best exploited by field extension functionaries and other stakeholders in enhancing level of adoption among farmers.
Keywords: Adoption; Chickpea; Cluster frontline demonstration; On farm trial; Scientific package of practices; Training